2014
DOI: 10.1007/s00406-014-0531-7
|View full text |Cite
|
Sign up to set email alerts
|

Gently restless: association of ADHD-like traits with response inhibition and interference control

Abstract: Impairment of inhibition-related functions is one of the most pronounced cognitive deficits found in attention-deficit/hyperactivity disorder (ADHD). Compelling evidence from studies of unaffected relatives of patients with ADHD and of ADHD-like traits in healthy subjects suggest the continuous distribution of ADHD symptoms in the population. A more subtle inhibitory deficit can also be found in healthy relatives of patients and in subjects with high ADHD-like traits. Here, we examined the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 90 publications
3
21
1
Order By: Relevance
“…They were slower than their controls and dyslexic children, and motor perseveration was more often seen compared to control, dyslexic and comorbid children. The latter type of error (tapping on the same plate twice) might be representative of difficulty inhibiting automatic responses which is a widely reported primary symptom associated with AD children [65, 68, 92]. This disinhibition is in line with Barkley’s hypothesis suggesting fragile inhibition control in AD populations.…”
Section: Discussionsupporting
confidence: 64%
“…They were slower than their controls and dyslexic children, and motor perseveration was more often seen compared to control, dyslexic and comorbid children. The latter type of error (tapping on the same plate twice) might be representative of difficulty inhibiting automatic responses which is a widely reported primary symptom associated with AD children [65, 68, 92]. This disinhibition is in line with Barkley’s hypothesis suggesting fragile inhibition control in AD populations.…”
Section: Discussionsupporting
confidence: 64%
“…4 A study on inhibition, an executive function whose impairments are part of the cognitive deficits seen in individuals with ADHD, demonstrated that performance on inhibition-related tasks were positively associated with ADHD-like traits in a large sample of healthy adults who did not have a first-degree relative with ADHD. 5 The heritability estimates for ADHD are essentially the same for both continuous and categorical approaches, consistent with a dimensional view of ADHD and a strong genetic component. [1][2][3]6 Based on the normal distribution of ADHD traits in the general population, the identification and understanding of ADHD susceptibility genes may bene fit from studies of this dimensional characteristic of ADHD in nonclinical samples.…”
Section: Introductionsupporting
confidence: 63%
“…Immediately before the experimental sessions, participants completed practice trials during which the experimenter ensured that instructions had been understood. The tasks are described in detail elsewhere (Aichert et al ., ; Polner, Aichert, Macare, Costa, & Ettinger, ).…”
Section: Methodsmentioning
confidence: 99%